2013
DOI: 10.1530/rep-12-0479
|View full text |Cite
|
Sign up to set email alerts
|

Summer heat stress affects prostaglandin synthesis in the bovine oviduct

Abstract: Summer heat stress (HS) negatively affects reproductive functions, including prostaglandin (PG) F 2a secretion in the endometrium, and decreases fertility in cattle. In the present study, we examined the effects of elevated temperatures on PG synthesis in oviductal epithelial cells. The epithelial cells obtained from the ampulla and isthmus of the oviduct were incubated at various temperatures (38.5, 39.5, 40.0, and 40.5 8C) for 24 h. In the ampulla, PGE 2 concentration was higher at 40.5 8C than at 38.5 8C, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 38 publications
1
37
1
1
Order By: Relevance
“…The mRNA and protein expression of HSP70 increased after 42°C heat treatment in cultured bovine mammary epithelial cells (Han et al 2014). Heat stress also induced HSP90 expression in bovine BMECs and the bovine oviduct (Kobayashi et al 2013;Deb et al 2014). Furthermore, we also found that heat stress increased the expression of HSP40 (also known as DNAJ proteins) in BMECs.…”
Section: Discussionsupporting
confidence: 55%
“…The mRNA and protein expression of HSP70 increased after 42°C heat treatment in cultured bovine mammary epithelial cells (Han et al 2014). Heat stress also induced HSP90 expression in bovine BMECs and the bovine oviduct (Kobayashi et al 2013;Deb et al 2014). Furthermore, we also found that heat stress increased the expression of HSP40 (also known as DNAJ proteins) in BMECs.…”
Section: Discussionsupporting
confidence: 55%
“…Our results differed from the report of [21] wherein they suggested that PGE 2 production was increased by elevated temperature in ampullary epithelial cells of cattle oviduct and the increased PGE 2 production could be due to either increases in the expressions of PGESs or increases in the PGES activity. It is concluded that in vitro heat stress altered prostaglandins, ionic and metabolic contents of sheep endometrial epithelial cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, Kobayashi [21] suggested that elevated temperature did not affect PGE 2 production in isthmic epithelial cells of cattle oviduct.…”
Section: Discussionmentioning
confidence: 96%
“…After removal of the infundibulum and the uterotubal junction, the oviduct was divided into two parts through the ampullary-isthmic junction, identified where the oviduct diameter first exhibited a marked reduction in size (going from ampulla to isthmus, Fig. 1) (Kobayashi et al 2013). The ampulla and isthmus of both the ipsilateral and contralateral oviduct were flushed with 500 μL PBS to confirm the presence of an unfertilized oocyte or an embryo under a microscope.…”
Section: Sample Collectionmentioning
confidence: 99%